2005
DOI: 10.1126/science.1108003
|View full text |Cite
|
Sign up to set email alerts
|

Differential Lysosomal Proteolysis in Antigen-Presenting Cells Determines Antigen Fate

Abstract: Antigen-presenting cells (APCs) internalize antigens and present antigen-derived peptides to T cells. Although APCs have been thought to exhibit a well-developed capacity for lysosomal proteolysis, here we found that they can exhibit two distinct strategies upon antigen encounter. Whereas macrophages contained high levels of lysosomal proteases and rapidly degraded internalized proteins, dendritic cells (DCs) and B lymphocytes were protease-poor, resulting in a limited capacity for lysosomal degradation. Consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

39
539
7
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 659 publications
(592 citation statements)
references
References 18 publications
39
539
7
7
Order By: Relevance
“…[4][5][6][7] Post AC engulfment, macrophages appear to be capable of fully digesting AC-associated antigens and limit their access to antigen presentation compartments, and therefore are inefficient at T-cell priming. 8 In contrast, DC are highly efficient at processing and presentation of engulfed antigens, using either direct or cross-presentation pathways, which either anergizes or activates potentially self-reactive T cells, depending on the context of antigen presentation. [9][10][11] Under homeostatic conditions, anti-inflammatory cytokines and natural regulatory T cells channel DC self-antigen presentation to induce regulatory T-cell differentiation from naïve CD4 T-cell precursors, and to tolerize effector CD8 T cells.…”
mentioning
confidence: 99%
“…[4][5][6][7] Post AC engulfment, macrophages appear to be capable of fully digesting AC-associated antigens and limit their access to antigen presentation compartments, and therefore are inefficient at T-cell priming. 8 In contrast, DC are highly efficient at processing and presentation of engulfed antigens, using either direct or cross-presentation pathways, which either anergizes or activates potentially self-reactive T cells, depending on the context of antigen presentation. [9][10][11] Under homeostatic conditions, anti-inflammatory cytokines and natural regulatory T cells channel DC self-antigen presentation to induce regulatory T-cell differentiation from naïve CD4 T-cell precursors, and to tolerize effector CD8 T cells.…”
mentioning
confidence: 99%
“…Importantly, several recent studies highlight the fact that lysosomal proteases can destroy as well as generate T-cell epitopes. DC express reduced levels of lysosomal enzymes compared with macrophages, which appear to improve rather than hinder their performance as APC [37]. They can also attenuate protease activity, at least in newly formed phagosomes, by raising phagosomal pH, which protected antigen for subsequent cross-presentation on class I MHC molecules [38].…”
mentioning
confidence: 99%
“…3a). Although both probes are highly specific for legumain in B cell lysates, recent studies have suggested that B cells contain lower levels of lysosomal protease activity than other antigen presenting cells [15]. We therefore decided to assess the potency and specificity of our ABPs in the murine monocytic cell line RAW264.7 (Fig 3b).…”
mentioning
confidence: 99%